Forsterite/nano-biogenic hydroxyapatite composites for biomedical applications. Issue 2 (2nd April 2020) - Naga, S.M.; Hassan, A.M.; Awaad, M.; Killinger, A.; Gadow, R.; Bernstein, A.; Sayed, M.
ABSTRACT: Recently, silicate materials have received attention as materials with promising applications in the bioceramics field. A recent study aimed to investigate the effect of forsterite (Mg2 SiO4 ) addition to biogenic hydroxyapatite, Ca10 (PO4 )6 (OH)2, on the phase formation, physical and mechanical properties, and biocompatibility of the produced composites. Different proportions of forsterite, 10 to 40 mass%, were added to hydroxyapatite obtained from fish bones to prepare the target composites. Various techniques, such as X-ray diffraction analysis (XRD), scanning electronic microscope (SEM), transmission electronic microscope (TEM), mechanical strength measurements and in vitro studies, were carried out to evaluate the composite properties. The results indicate that the addition of 20 to 40 mass% forsterite led to the transformation of forsterite into protoenstatite and the formation of Mg-rich whitlockite at the expense of hydroxyapatite. It is concluded that 20 mass% forsterite is the optimum addition amount to enhance the physical and mechanical properties of the produced composites. The cell culture tests and in vitro studies agree with the abovementioned results. Graphic abstract: